Are MS in economics programs in departments that also have a PhD program in economics different from their counterparts?. Issue 3 (2nd July 2016) - Milkman, Martin I.; Marjadi, Riza; McCoy, James P.
ABSTRACT: This is the first article that compares terminal master's degree programs in economics from universities that have a PhD program in economics with those that do not offer PhD programs in economics. The authors compare these differences based on surveys in 2002 and 2012. They examine differences in general program characteristics, department faculty, admission requirements, student characteristics, financial aid, and graduation and placement rates. They find statistically significant differences in all of these categories and also find that some of the differences and similarities have changed over time.